The Impact of Managerial Change on Performance. The Role of Team Heterogeneity - Gerd Mühlheußer; Dirk Sliwka; Sandra Hentschel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
When a key responsibility of a manager is to allocate more or less attractive tasks to subordinates, these subordinates have an incentive to work hard and demonstrate their talents. As a new manager is less well acquainted with these talents this incentive mechanism is reinvigorated after a management change but only when the team is sufficiently homogenous. Otherwise, a new manager quickly makes similar choices as the old one did. We investigate this hypothesis using a large data set on coach dismissals in the German football league where the selection of players is indeed a key task of the coach. Indeed, we find substantial evidence that coach replacements enhance team performance (only) in homogenous teams. Moreover, from a methodological point of view, we argue that there is typically a negative selection bias when evaluating succession effects, which might reconcile previous findings of no (or even negative) effects with the vast number of dismissals observed in reality.
Keywords: D22; J44; J63; 330